Compositionality in al-Farabi - bahaodin movahhed abtahi; lotfo allah nabavi; mohammad ali hojati (حکمت اسرا)
Compositionality is an important principle in new semantics. On this principle, the meanings of compound words are determined by the meaning of its parts and the way in which how to be composed. Every system of semantics must be compositional on a priory arguments of this principle. The history of the principle usually returned to Frege but the supreme status of Muslim thinkers has been forgotten. So al-Farabi as a great Muslim thinker is a good candidate. In the article, I tried to introduce a suitable conceptual framework in al-Farabi for research in compositionality. Then to separate epistemological compositionality from semantic one and based on pragmatic approach, we study al-Farabi's speaks. It seems that al-Farabi accepts at least some of explanations of compositionality.